Highly tailored gap-like structure for excellent thermoelectric performance - Xu, Xiao; Huang, Yi; Liu, Xixi; Jia, Baohai; Cui, Juan; He, Ran; Wang, Jinghan; Luo, Yiyuan; Nielsch, Kornelius; He, Jiaqing (Energy and Environmental Science, 2022)
The microstructure-dependent thermal transport property has drawn significant attention in the thermoelectric community for elevating thermoelectric performance. In this work, we characterized gap-like structures and improved their controllability in GeTe-rich Sb2Te3(GeTe)n samples. The statistics of the gap-like structures were studied through direct observation using a transmission electron microscope with atomic-resolved spherical aberration correction. We found a strong and unambiguous linear correlation of the nominal composition to the planar density and sizes of the gap-like structures. This microstructure tailoring further enabled a significant reduction in lattice thermal conductivity, an ultrahigh maximum ZT value of ∼2.4 at 773 K, and an average ZT value of ∼1.51 from 323 K to 773 K in p-type Sb2Te3(Ge0.995Yb0.005Te)17. Together with n-type Pb0.985Sb0.015Te, we further fabricated a single-stage thermoelectric module that realized an exceptional output power density value of 1.25 W cm−2 and an efficiency of 7.5% under a temperature gradient of 480 K. Our pioneering strategy validated the beneficial effect of gap-like-structure tailoring for improving thermoelectric performance, laying the groundwork for similar studies on other thermoelectric materials.
CRIS-Team Scopus Importer:2023-03-20